New records of the Genus Festuca L. (Poaceae) for Colombia and Venezuela New records of the Genus Festuca L. (Poaceae) for Colombia and Venezuela - Stancik Daniel (Caldasia)
The genus Festuca L. (Poaceae) includes about 350-400 herbaceous species with wide cosmopolitan distribution (Watson & Dallwitz 1992). The center of distribution ofthe genus is in the meadows and steppes of North America and Eurasia. Sorne species are present in Australia, Tasmania, New Zealand, and W and SE Africa. High species diversity is found in the pampas of Argentina and the puna of the Andes, with approximately 40 species in Peru (Tovar 1993),30 in Bolivia (Renvoize 1998), and 30 in Argentina (Türpe 1969). So far, 26 native species are known from the páramos of the northern South America; about seven new species from this region will be described soon (author's unpublished data). The genus Festuca L. (Poaceae) includes about 350-400 herbaceous species with wide cosmopolitan distribution (Watson & Dallwitz 1992). The center of distribution ofthe genus is in the meadows and steppes of North America and Eurasia. Sorne species are present in Australia, Tasmania, New Zealand, and W and SE Africa. High species diversity is found in the pampas of Argentina and the puna of the Andes, with approximately 40 species in Peru (Tovar 1993),30 in Bolivia (Renvoize 1998), and 30 in Argentina (Türpe 1969). So far, 26 native species are known from the páramos of the northern South America; about seven new species from this region will be described soon (author's unpublished data).